Why research-informed teaching in engineering education? A review of the evidence. (4th May 2017) - Bubou, Gordon Monday; Offor, Ibebietei Temple; Bappa, Abubakar Saddiq
ABSTRACT: Challenges of today's engineering education (EE) are emergent, necessitating calls for its reformation to empower future engineers function optimally as innovative leaders, in both local and international contexts. These challenges: keeping pace with technological dynamism; high attrition; and most importantly, quality teaching/learning require multifaceted approaches. But how can EE respond to the growing demand for relevant teaching? What can we do for engineering faculties to leverage on quality teaching? How do we embed quality teaching in EE? Scholarship of teaching and learning is advocated as one viable approach. It uses evidence-based teaching (EBT) strategies, and research-informed evidence to guide educational decisions regarding teaching and learning. We review the theories underpinning EBT, the scientific evidence on which it is based, and innovative instructional strategies that enhance active learning. Some of these issues have been discussed already, largely through developing countries lens. Nevertheless, linkages to equivalent global perspectives are presented here.